2012
DOI: 10.1002/jbmr.1608
|View full text |Cite
|
Sign up to set email alerts
|

Absence of sclerostin adversely affects B-cell survival

Abstract: Increased osteoblast activity in sclerostin‐knockout (Sost−/−) mice results in generalized hyperostosis and bones with small bone marrow cavities resulting from hyperactive mineralizing osteoblast populations. Hematopoietic cell fate decisions are dependent on their local microenvironment, which contains osteoblast and stromal cell populations that support both hematopoietic stem cell quiescence and facilitate B‐cell development. In this study, we investigated whether high bone mass environments affect B‐cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 59 publications
7
76
0
Order By: Relevance
“…It has been demonstrated that targeted disruption of sclerostin results in a decreased number of B cells due to elevated Bcell apop tosis. 40 As sclerostin is primarily expressed in osteocytes and is not expressed in any haematopoietic lineages, the Bcell defect in these mice was caused by the impaired pro duction of sclerostin by osteocytes. 40 These results suggest a novel role of osteocytes in the regulation of bone marrow environments that support immunological cells.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…It has been demonstrated that targeted disruption of sclerostin results in a decreased number of B cells due to elevated Bcell apop tosis. 40 As sclerostin is primarily expressed in osteocytes and is not expressed in any haematopoietic lineages, the Bcell defect in these mice was caused by the impaired pro duction of sclerostin by osteocytes. 40 These results suggest a novel role of osteocytes in the regulation of bone marrow environments that support immunological cells.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…In addition, noncanonical Wnt signaling is also reported to sustain HSCs maintenance and aging [20,21]. Osteoblasts also support B-cell commitment and differentiation [22][23][24]. However, the function of Wnt signaling in osteoblastsupported B-cell development remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblasts also support B-cell commitment and differentiation [22][23][24]. However, the function of Wnt signaling in osteoblastsupported B-cell development remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elimination of SOST gene expression prevented the depletion of Sca-1 ϩ -expressing bone marrow cells caused by Pb exposure. The drop in total Sca-1 ϩ MSCs in SOST-KO mice was not surprising given the bony overgrowth that occurs in animals devoid of sclerostin that narrows the marrow cavity (38). MSCs harvested from SOST-KO mice were less susceptible to Pb toxicity, showing improved osteoblastic activity.…”
Section: Discussionmentioning
confidence: 93%